Teachers' Efforts In Incorporating Religious Character In Students Through Al-Qur'an Reading Activities At Mis Humaira, Bengkulu City - Dwi Putri Oktaviani; Nadia Wulandari; Ahmad Suradi; Adam Nasution (International Journal on Advanced Science, Education, and Religion, 2025)
This research is motivated by the importance of forming religious character of students since elementary school age through habitual activities of reading the Qur'an in the school environment, however, various problems are still found such as differences in student reading abilities, lack of motivation, and environmental and technological influences that can hinder the process of internalizing religious values. This study aims to describe the efforts of teachers in instilling religious character, analyze the implementation of Qur'an reading activities in forming student character, and identify supporting and inhibiting factors in its implementation at MIS Humaira Bengkulu City. The method used is qualitative with a descriptive approach, with research subjects of teachers, students, and parents selected by purposive sampling. Data collection techniques through observation, interviews, and documentation, while data analysis is done through data reduction, data presentation, and drawing conclusions with triangulation of sources and techniques. The results of the study indicate that teachers make efforts through habitual reading of the Qur'an, role models, motivation, and individual guidance, as well as routine Qur'an reading activities every morning are able to shape student character such as discipline, responsibility, calmness, and religious attitudes. Supporting factors include the active role of teachers, school support, and routine practice, while inhibiting factors include students' uneven reading ability, lack of parental guidance, and the influence of gadgets. In conclusion, Quran reading activities are effective in instilling religious character in students if carried out consistently and supported by various parties, and have important implications for the roles of teachers, schools, and parents in the ongoing development of student character.